Saccharification of chitin using solid-state culture of Aspergillus sp. S1-13 with shellfish waste as a substrate - Rattanakit N. (2014)
Saccharification of chitin was performed in a suspension (mash) of a solid-state culture of chitinase-producing Aspergillus sp. S1-13 with acid-treated shellfish waste as a substrate. The conditions for the saccharifying reaction and the solid-state cultivation were examined from the view-point of saccharification in the mash. Optimum cultivation conditions were defined: a solid-state medium consisting of 5 g of 10% lactic acid-treated crab shells (0.50-2.36 mm in size) and 3 ml of a basal medium (0.028% KH2PO4, 0.007% CaCl2·2H2O, and 0.025% MgSO4·7H2O) supplemented with 0.3% peptone was inoculated with 4 ml of spore suspension (1×107 spores/ml), and the water content of the medium was adjusted to 75%; static cultivation at 37°C for 7 d. When a culture obtained under the optimum conditions was suspended in 70 ml of 50 mM sodium phosphate-citrate buffer (pH 4.0) and incubated at 45°C for 11-13 d, 55 mM N-acetylglucosamine (GlcNAc) was formed in the solid-state culture mash, indicating that at least 33% of the initial chitin in the solid material was hydrolyzed. Through the experiments, the amounts of GlcNAc formed in the solid-state culture mash varied in a way similar to that of the water-extractable p-nitrophenyl β-D-N-acetylglucosaminide-hydrolyzing enzyme in the culture, but not to that of the colloidal chitin-hydrolyzing enzyme. GlcNAc-assimilating lactic acid bacteria, which were inoculated into the mash after or at the start of the saccharification, formed lactic acid with decreasing GlcNAc.